Loss in tocopherols and oxidative stability during the frying of frozen cassava chips - Corsini, Mara S. [UNESP]; Silva, Marta G.; Jorge, Neuza [UNESP] (Inst Grasa Sus Derivados, 2009)
The present study was aimed at verifying tocopherols losses and oxidative stability changes in vegetable oils used in discontinuous frying. The frying of frozen cassava chips was carried out in a household electric frying pan, where the oil was heated to a temperature of 180 degrees C for 25 hours, with fresh oil replacement. The results obtained from the analytical determinations were submitted to variance analysis, in a factorial scheme, using a completely randomized design, making it possible to determine the influence of the type of oil and frying times on changes in the oil. The data show that the smallest changes occur in palm oil, which is more saturated. For sunflower and cottonseed oils, which are more unsaturated, there was a clear decrease in both tocopherol concentration and oxidative stability.
Keywords: Antioxidants; Oxidative stability; Tocopherols; Vegetable oils